The development of academic literacy in the first-year psychology course at Rhodes University: an assessment of the tutorial programme - Amos, Trevor Lawrence (Rhodes University, Faculty of Humanities, Department of Psychology, 1998)
This research is concerned with the cognitive development of students in higher education. Specifically, it is recognised that the demands facing students are different to those previously encountered in secondary education. These demands include being able to master what Strohm Kitchener (1983) calls ill-structured problems and learning the groundrules of their academic disciplines. This is termed academic literacy. Current thought in academic development proposes that students need to be shown how to mobilise their cognitive processes to meet these demands. It is argued that this is best accomplished when such activities are integrated into the discipline itself as opposed to being an add-on process. Taking into account the social and dialectical nature of learning (Vygotsky, 1978), academic development and academic literacy are seen to best occur within the tutorial system. The purpose of this research was to evaluate the 1997 first-year Psychology tutorial programme at Rhodes University, Grahamstown to assess how academic literacy was being developed. A qualitative research approach was followed, guided by the ten stage evaluation model of education programmes (Jacobs, 1996) and an adapted version of the Context, Input, Process and Product approach to evaluation (Parlett and Hamilton cited in Calder, 1995, p.25). Using indepth interviews, data was gathered from eight first year students, seven staff members and one programme co-ordinator. Focus groups were used to gather data from nine tutors. Further data collection techniques included observation of tutor briefing sessions and tutorials as well as documentary research. Data was analysed using qualitative data analysis techniques (Coffey & Atkinson, 1996). The Psychology Department at Rhodes University aims to integrate the development of academic literacy into mainstream teaching at the first year level through its tutorial programme. The Department has conceptualised its understanding of academic development as the development of academic, vocational and professional literacy which is rather unique. Academic literacy is defined and conceptualised further in a list of pre-determined skills (reading, writing and general skills) to be developed incrementally. This conceptualisation of academic literacy tends to neglect to include the mobilisation of relevant cognitive processes explicitly and the implementation tends to remain implicit. A lack of tactical strategies to implement academic development is evidence of the difficulty in moving from the philosophical level of academic development to the practical level. The programme is perceived as disorganised and lacking in a co-ordinated or incremental development of the predetermined skills.
Keywords: Psychology -- Study and teaching (Higher); Psychology -- Study and teaching (Higher) -- South Africa; Academic achievement -- South Africa; College student development programs -- South Africa